Acoustic cues, not phonological features, drive vowel perception: Evidence from height, position and tenseness contrasts in German vowels - Llompart Garcia, Miguel; Reinisch, Eva (Journal of Phonetics, 2018)
Phonological features have frequently been singled out as the units of perception, especially for vowels. Evidence of the use of features has been provided for vowel height and vowel position, which have one acoustic correlate only. However, findings on acoustically complex features such as tenseness are less clear. The present study assessed the role of phonological features in perception using the selective adaptation paradigm. Selective adaptation effects on German vowel contrasts differing in vowel height (Experiment 1), position (Experiment 2) and tenseness (Experiment 3) were examined. We tested how the categorization of each vowel contrast was affected by adaptation to words containing vowels that differently resembled or diverged from the vowels in the critical contrast acoustically and in terms of their phonological feature specifications. Results showed that selective adaptation patterns could be predicted by the vowels' phonological features for the height and position contrasts, but not for the tenseness contrast. However, adaptation patterns for the latter can be explained by the relationship between adaptors and continuum endpoints in each of the relevant acoustic cues to the contrast. This suggests that vowel perception may be dependent on these acoustic cues rather than phonological features.
Keywords: Vowels; Pre-lexical units; Phonological features; Acoustic cues; Speech perception; Selective adaptation